Congenital Disorders of Glycosylation: What Clinicians Need to Know? - Lipiński, Patryk; Tylki-Szymańska, Anna (Frontiers in Pediatrics, 2021)
Congenital disorders of glycosylation (CDG) are a group of clinically heterogeneous disorders characterized by defects in the synthesis of glycans and their attachment to proteins and lipids. This manuscript aims to provide a classification of the clinical presentation, diagnostic methods, and treatment of CDG based on the literature review and our own experiences (referral center in Poland). A diagnostic algorithm for CDG was also proposed. Isoelectric focusing (IEF) of serum transferrin (Tf) is still the method of choice for diagnosing N-glycosylation disorders associated with sialic acid deficiency. Nowadays, high-performance liquid chromatography, capillary zone electrophoresis, and mass spectrometry techniques are used, although they are not routinely available. Since next-generation sequencing became more widely available, an improvement in diagnostics has been observed, with more patients and novel CDG subtypes being reported. Early and accurate diagnosis of CDG is crucial for timely implementation of appropriate therapies and improving clinical outcomes. However, causative treatment is available only for few CDG types.